“JISMONIY TARBIYA KADRLARINING KASBIY VA MILLIY-GUMANITAR SALOHIYATINI OSHIRISH” (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Another main task that fundamentally changes the quality of physical education is the function of turning education into a real mechanism of physical, moral and mental development of a person[1,3]. Strengthening the role of the individual in all areas of social development is a very important task of fundamentally changing the physical education system as the main source of healthy human potential of the society. To carry out these tasks, specialists with a high pedagogical and scientific-research culture, who are capable of professional creativity in the broad sense, are required in the field of physical education and sports. [2,5].